Preliminary Investigation: Students’ English Achievement During and Post Covid-19 Pandemic - Khadijah Maming; Achmad Abdul Choliq; Nasrullah A. (Musamus Journal of Language and Literature, 2023)
The covid-19 issue has altered the educational atmosphere; the learning process is now done online. However, post-pandemic situations covid-19 altered the learning context once more. This research was carried out to determine students' expectations about learning English. In particular, this study aims to find out what students accomplished in English learning during and after the covid-19 pandemic. The qualitative design was adopted in this investigation. The researchers used a descriptive qualitative technique in their investigation. The students from UPT SD Negeri 126 Pinrang, specifically the fourth grade of elementary school were the subjects of this study with the total subjects were twenty-two students. The researchers gathered data from fourth graders’ English scores, which they acquired directly from the fourth-grade homeroom instructor. The achievement of student achievement during covid-19 pandemic, which was compared to the achievement of student scores following covid-19 pandemic, turned out to be lower than what the researchers predicted; several variables contributed to this, and this is what researchers can use for future research.